Feminist Collections, v.18, no.1 (fall 1996) - (:unkn) unknown (My University, 1996)
Subtitle: A Quarterly of Women's Studies Resources. 46p.
Contents: FROM THE EDITORS. BOOK REVIEWS: Global Feminism, by Kathleen Mulligan-Hansel. The Politics of Feminist Theory, by Eleanor M. Miller. The Voices and Lives of Latin American Women Writers, by Carole Byrd. FEMINIST VISIONS: Saltara/Diving into Chicana Identity, by Diane Soles and Shattering Stereotypes: Spiderwoman Theatre, by Faye Flesia. ARCHIVES. NEW AVENUES IN WOMEN'S STUDIES RESEARCH: USING PUBLIC RECORDS by Brenda L. Burk. FEMINIST PUBLISHING. COMPUTER TALK: Compiled by Linda Shult. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Reviewed by Phyllis Holman Weisbard. PERIODICAL NOTES: Compiled by Linda Shult. ITEMS OF NOTE: Compiled by Renee Beaudoin. BOOKS RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews; Global Feminisms; Feminist Theory; Latin American Women Writers; Using Public Records in Women's Studies Research; Chicana Identity; Native American Women's Theatrical Group